2004
DOI: 10.1093/carcin/bgh333
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of the receptor for advanced glycation end-products (RAGE) supports non-small cell lung carcinoma

Abstract: The receptor for advanced glycation end-products (RAGE) is a transmembrane receptor of the immunoglobulin superfamily. Several ligands binding to RAGE have been identified, including amphoterin. Experimental studies have given rise to the discussion that RAGE and its interaction with amphoterin contribute to tumour growth and metastasis. However, none of the studies considered a differential transcription profile in cancer that might change the interpretation of the study results when comparing RAGE in tumours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
116
2
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(127 citation statements)
references
References 36 publications
8
116
2
1
Order By: Relevance
“…These observations are at variance with data obtained with glioma, melanoma, colon cancer, and human pancreatic carcinoma cells, 24 -27 in which a positive correlation was found among RAGE expression, neoplastic transformation, and metastasis, but are consistent with the differentiating activity of HMGB1/RAGE in neurons and L6 myoblasts. 11,34 However, our data are consistent with observations made with non-small lung carcinoma cells, 58 in which down-regulation of RAGE was found to be associated with neoplastic transformation and with previous work showing that RAGE-induced neuronal differentiation is associated with proliferation arrest. 26 The reduced proliferation of TE671/RAGE cells in vitro compared with TE671/wt and TE671/RAGE⌬cyto cells is accompanied by an increased induction of the proliferation inhibitor p21 WAF1 and remarkably decreased levels of cyclin D1 and extent of ERK1/2 and Rb phosphorylation.…”
Section: Discussionsupporting
confidence: 92%
“…These observations are at variance with data obtained with glioma, melanoma, colon cancer, and human pancreatic carcinoma cells, 24 -27 in which a positive correlation was found among RAGE expression, neoplastic transformation, and metastasis, but are consistent with the differentiating activity of HMGB1/RAGE in neurons and L6 myoblasts. 11,34 However, our data are consistent with observations made with non-small lung carcinoma cells, 58 in which down-regulation of RAGE was found to be associated with neoplastic transformation and with previous work showing that RAGE-induced neuronal differentiation is associated with proliferation arrest. 26 The reduced proliferation of TE671/RAGE cells in vitro compared with TE671/wt and TE671/RAGE⌬cyto cells is accompanied by an increased induction of the proliferation inhibitor p21 WAF1 and remarkably decreased levels of cyclin D1 and extent of ERK1/2 and Rb phosphorylation.…”
Section: Discussionsupporting
confidence: 92%
“…In colon cancer, joint expression of RAGE and HMGB1 was found to lead to enhanced migration in the cancer cell line, and the level of expression of RAGE and HMGB1 increased with the stage of cancer (12). By contrast, in lung cancer, a higher tumor stage was reported to be characterized by a downregulation in RAGE expression at the mRNA and protein levels (7). The present study confirmed that the expression of RAGE was downregulated in lung cancer tissue compared with noncancerous tissue from the same patient.…”
Section: Discussionmentioning
confidence: 99%
“…Normal ATI cell differentiation and phenotype [22,50,51] Normal: embryonic stages [50,51] Tumorigenesis: cancer cell regression to embryonic phenotypes [37,[52][53][54][55][56][57][58] Normal ATI cell adhesion, spreading and stability [22] Decreased adhesiveness, increased migration, enhanced invasiveness [15,22,37,59-61] Normal alveolar cell apoptosis Evasion of apoptosis [15,16,29,59, 60] Normal alveolar function -gas exchange [22,62] Malignant behavior [59,60,61,63] Normal lung architecture [22,64] Malignant tissue and tumor stroma reorganization and modification [15,16,29,59-61] Normal cell-to-cell and cell-to-matrix communication Disruption of normal communication -cell isolation and autonomy explain the difference in binding affinity between different ligands, since each one of them possesses its own specific electrostatic signal. Touré et al showed that neutrophils exhibit enhanced adhesiveness and decreased migration on AGE-modified collagen in comparison to non-modified collagen [68].…”
Section: Normal Rage Expression Suppressed Rage Expressionmentioning
confidence: 99%
“…Lung cancer, one of the most invasive malignancies, expresses low levels of RAGE [37], which correlate positively to increased tumor growth and invasiveness [59,60]. Furthermore, RAGE genes may have a role in the diagnosis of lung neoplasms, since they can be employed for the discrimination between normal and malignant lung tissues [96,97].…”
Section: Role Of Rage In Lung Cancermentioning
confidence: 99%
See 1 more Smart Citation